Development questionnaire about High school students learning scienceand technology in the 21st century (International Conference on Computers in Education, 2013)
This study revised three surveys. The development of questionnaires was focused on three major themes: 21stcenturylearning ability, Teacher Authority Survey (TAS), and Self-efficacy.Firstly, 21stcenturylearning ability is the relationships among students’ perceptions for collaborative learning, critical thinking, self-directed learning, creative thinking, meaningful use of Information and communication Technology (ICT), problem solving, knowledge creation efficacy, design disposition, teacher authority, and learning achievements. And, secondly, name Learning in schools and the preferred version of TASquestionnaire, and utilize both of them to elicit high school students’ conceptions of learning and preferences of teacher authority in classroom. The study aims to develop a questionnaireto explore High school students’ learning science and technologyin the 21st century.